Inside Advertiser and Agency Relationships: A Hands-On Guide for Practitioners - Prince, Melvin; Davies, Mark (Lulu. com, 2006)
Keywords: dept.mkt

A study of hofstede's culture value survey in a post-soviet country - Kustin, Richard Alan (Journal of Transnational Management, 2006)
This research examines the four culture dimensions developed by Hofstede's 1980 and 1983 studies exploring the potential of management-employee conflict. In the present study, employee responses to Hofstede's national culture survey were performed in Belarus, formerly of the Soviet Union, in order to establish a culture score for each of Hofstede's four culture dimensions in a centrally planned economy. The results of the research run counter to some of the stereotypic cultural characteristic expectations, and support others of the cultural values attributable to the Republic of Belarus, an autocratic political and economic state in Eastern Europe. Copyright © by The Haworth Press, Inc. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-436-842-989-159 tex.type: [object Object]
Keywords: Belarus; Cross culture; Cultural survey; Culture dimensions; Eastern Europe; Eurasia; Europe; Hofstede; International management; culture; dept.mkt; geographical research; survey